2018
DOI: 10.1002/cbin.10989
|View full text |Cite
|
Sign up to set email alerts
|

TRIM22 knockdown suppresses chronic myeloid leukemia via inhibiting PI3K/Akt/mTOR signaling pathway

Abstract: Tripartite motif-containing 22 (TRIM22) is reported to participate in numerous cellular activities. Recent studies confirm that TRIM22 is a target gene for P53, and inhibits clonogenic growth of leukemic U-937 cells. The current study aims to discover the effect of TRIM22 in progression of human chronic myeloid leukemia (CML) and explore the related mechanism. TRIM22 was knocked down by siRNA transfection in CML cell K562. We observed that TRIM22 knockdown decreased proliferation and invasion in K562 cells. TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%
“…Secondly, PTEN plays critical roles in regulating not only hematopoietic stem cell activity through a Niche-dependent mechanism, but also hematopoiesis and leukemogenesis [341][342][343]. Furthermore, TAL1, c-Jun, EZH2, TRIM22, ETV6/RUNX1, miR-7, -22, -26b, -103, -125b, -126, -139-5p, -181c, -193a, -628, and -3142, as well as LncRNA HULC, UCA1, linc00239 and LINC00265 control leukemogenesis, proliferation, apoptosis or chemoresistance via PI3K/AKT pathway [344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359][360][361][362][363]. Hereafter, PI3K/AKT pathway inhibition is regarded as a therapeutic approach [364,365] followed by the preclinical studies in leukemia cells [366,367] in spite of the upregulated expression of P2RY14 in acute leukemia cells resistant to PI3K/ mTOR inhibition [368].…”
Section: (Nct01002248; Nct01476137; Nct00881946) (Tables 2 and 3)mentioning
confidence: 99%
“…6,7 Some members are thought to be important regulators of carcinogenesis. 8,9 Among these members, TRIM22 has been proved to be involved in various cancers, such as endometrial cancer, 10 leukemia, 11 non-small cell lung cancer, 12 and breast cancer. 13 However, the role of TRIM22 in glioma has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TRIM22 downregulation significantly induces cell cycle arrest by regulating the levels of CDK4, cyclin D1, P70S6K and P53 in K562 cells. 52 In summary, these findings indicate that HMGA2 might be a functional target of miR-4651 in the regulation of cell proliferation in GMSCs under NIF stimulation, and the miR-4651-HMGA2 signalling pathway may be involved in the process of NIGO. To our knowledge, this is the first study to examine the role of miR-4651 and HMGA2 in regulating proliferation in NIGO.…”
Section: Discussionmentioning
confidence: 71%